Spatial Analysis of Health Services in Kassala State - أ . د/ عرض حاج علي; د.مناهلإدريسأدروبعنجة (White Nile Journal for Studies and Research, 2026)
This study was to address the issue of spatial analysis of health services in kassala state, The main objective of this study is to analyze the current spatial distribution of health services and their suitability for spatial planning standards that meets the needs of the community in the kassala state. The methodology of study followed the descriptive and analytical approach based on the results of the results of a comprehensive field survey carried out by author for public health services, hospital and health centers, including the health center and pharmacies in the study area, in